Intelligent Portable Traffic Light - Monica, Josephine (2016)
The traffic at the vicinity of construction site is managed by a few people holding stop and go signs. This manual approach has at least two draw backs: Waste of human resources. Limited communication between the two faraway workers (especially in a big construction area). By developing “Intelligent Portable Traffic Light”, we will be able to eliminate these problems. [2nd Award]